2020
DOI: 10.1107/s2056989020013341
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(II) carbonyl, ammonia, and acetonitrile complexes supported by a pyridine dipyrrolide pincer ligand

Abstract: The synthesis, isolation and crystal structures of nickel(II) carbonyl, acetonitrile and ammonia complexes supported by a dianionic, pyridine dipyrrolide pincer ligand [pyrr2py]2−, namely, carbonyl[2,2′-(pyridine-2,6-diyl)bis(3,5-di-p-tolylpyrrolido-κN)]nickel(II), [Ni(C41H33N3)(CO)], ammine[2,2′-(pyridine-2,6-diyl)bis(3,5-di-p-tolylpyrrolido-κN)]nickel(II), [Ni(C41H33N3)(NH3)], and (acetonitrile-κN)[2,2′-(pyridine-2,6-diyl)bis(3,5-di-p-tolylpyrrolido-κN)]nickel(II), [Ni(C41H33N3)(CH3CN)], as well as the free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Of late, a new family of tridentate pincer ligands, so called pyridine dipyrrolides (PDPs) in their dianionic, doubly deprotonated form (PDP 2– ), has garnered widespread attention in both transition metal and main group chemistry. Because H 2 PDP proligands are prepared in a modular fashion, the corresponding PDP 2– ligands are well suited for the manipulation of specific steric and electronic profiles of coordinated metals. With this in mind, researchers have leveraged PDP metal complexes in catalysis, atom and group transfer, ,, and photochemistry. Despite this expanding wealth of research, PDP compounds of either lanthanide or actinide elements have not been reported …”
Section: Introductionmentioning
confidence: 99%
“…Of late, a new family of tridentate pincer ligands, so called pyridine dipyrrolides (PDPs) in their dianionic, doubly deprotonated form (PDP 2– ), has garnered widespread attention in both transition metal and main group chemistry. Because H 2 PDP proligands are prepared in a modular fashion, the corresponding PDP 2– ligands are well suited for the manipulation of specific steric and electronic profiles of coordinated metals. With this in mind, researchers have leveraged PDP metal complexes in catalysis, atom and group transfer, ,, and photochemistry. Despite this expanding wealth of research, PDP compounds of either lanthanide or actinide elements have not been reported …”
Section: Introductionmentioning
confidence: 99%